Evaluation of post-heating flexural behavior of steel fiber-reinforced high-strength concrete beams reinforced with FRP bars: Experimental and analytical results - Jafarzadeh, Hamed; Nematzadeh, Mahdi (Engineering structures, 2020)
•Post-fire flexural behavior of fibrous concrete beams reinforced with GFRP bar was studied.•Key variables consisted of the temperature, fiber volume fraction, and reinforcement ratio.•An analytical model was developed to capture load-deflection relationship of heated beam specimens.•Exposing the beams to 400 °C increased the residual load-carrying capacity notably.•Exposing the beams to 600 °C led to severe degradation in the flexural capacity. Despite many advantages provided by fiber-reinforced polymer (FRP) bars, their low resistance against fire has been an important barrier for their widespread application in reinforced concrete (RC) members. Studying the post-fire performance of concrete structures reinforced with FRP bars can be beneficial in understanding the structural safety and estimating the serviceability conditions after a fire incident. Since little information is available in the literature in this regard, especially for high-strength concrete (HSC) and fiber-reinforced concrete (FRC), this research attempted to investigate the flexural behavior of HSC beams reinforced with glass fiber-reinforced polymer (GFRP) bar and steel fibers after exposure to elevated temperatures. The variables under consideration consisted of the applied temperature (20, 250, 400, and 600 °C), volume ratio of steel fibers (0 and 1%), and reinforcement ratio (0.314 and 0.872%). Following the quasi-static four-point flexural test on the heated and non-heated beam specimens, various parameters involving the load-carrying capacity, load-deflection relationship, cracking pattern in terms of the number and width of cracks at service and ultimate loads, and ductility of the beams were examined. It was found that exposing the beams to 250 °C reduced their load-carrying capacity negligibly and exposing them to 400 °C increased their residual load-carrying capacity notably while exposing them to 600 °C led to severe degradation in their flexural capacity. Further, the effectiveness of steel fibers on the behavior of beams with the lower reinforcement ratio was not significant; however, as the reinforcement ratio of the beams and applied temperature increased, steel fibers properly demonstrated their ability in improving the load-carrying capacity and reducing deflection at service load. By evaluating prediction relationships provided by codes and other researchers against the experimental results observed in this research, ACI 440.1R-06 and ACI 440.1R-15 codes were found to be able to predict deflection under service conditions with proper accuracy. Ultimately, for capturing the load-deflection relationship of heated and non-heated beam specimens, an analytical model was developed using the sectional analysis method, which was able to predict the experimental results appropriately.